Gemeinsam den Geographieunterricht der Zukunft andenken. Ein idealtypisches Modell für eine kompetenzorientierte Lehrerbildung in der Geographiedidaktik - Hemmer, Michael; Uphues, Rainer (Zeitschrift für Geographiedidaktik (ZGD), 2011)
The reform of teacher training within the Bologna process provides the opportunity to rethink the geographic-didactical education of German universities. Based on central didactical documents (e.g. standards for teacher training from the ministry of education) and empiric knowledge approaches of a renewed training concept for geography didactics are developed. Following, these approaches are presented within an ideal model of a competence-orientated teacher training. The model consists of 5 steps of progression. For each step the aimed competence focus and different forms of competence diagnostics are described. Furthermore all steps are illustrated with innovative examples.
Keywords: teacher training, skills, didactical theory, higher education, reflexive learning, learning progression